Growth and Aging of Proximal Femoral Bone: A Study With Women Spanning Three Generations. (16th February 2015) - Wang, Qin; Chen, Decai; Cheng, Shu Mei; Nicholson, Patrick; Alen, Markku; Cheng, Sulin
ABSTRACT: Osteoporotic hip fracture is a serious clinical event associated with high morbidity and mortality. Understanding femoral growth patterns is important for promoting bone health in the young and preventing fractures in later life. In this study, growth patterns of areal bone mineral density (aBMD) and geometric properties of the proximal femur were measured by dual‐energy X‐ray absorptiometry. They were studied in 251 girls from premenarche (11.2 ± 0.7 years) to late adolescence (18.3 ± 1.1 years) and compared with their premenopausal mothers ( n  = 128, aged 44.9 ± 4.1 years) and postmenopausal grandmothers ( n  = 128, aged 70.0 ± 6.3 years). Hip axis length (HAL) was the first to reach peak growth velocity (−10.5 months before menarche), followed by neck diameter (ND) and neck cross‐sectional area (CSA), (−7.1 and −4.1 months before menarche, respectively). Both neck‐shaft angle (NSA) and aBMD of neck and total hip peaked at menarche. At 18 years (7‐year follow‐up), girls already had higher femoral neck aBMD but similar HAL and NSA compared with their mothers. Grandmothers had the longest HAL, narrowest NSA, widest ND but lowest aBMD and CSA. Hip strength index (HSI), an index of femoral neck strength during a fall, dropped rapidly after menarche in girls but thereafter remained relatively constant. Grandmothers had lower HSI than either mothers or girls. In conclusion, differences in proximal femoral bone mass and structure in adulthood are largely established before menarche, indicating that heritable factors are responsible for most of the individual variance. The development of geometric properties precedes aBMD in puberty, resulting in relatively constant hip strength after menarche. This asynchronous growth leads to adaptation of bone strength to the imposed loads, avoiding fractures in a biologically efficient manner. Both deterioration of aBMD and inadequate compensatory change in bone geometry after menopause contribute to the increased fracture risk later in life. © 2014 American Society for Bone and Mineral Research.